2014
DOI: 10.1017/s003118201400050x
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal assessment of the serological response toTheileria parvaand other tick-borne parasites from birth to one year in a cohort of indigenous calves in western Kenya

Abstract: SUMMARYTick-borne diseases are a major impediment to improved productivity of livestock in sub-Saharan Africa. Improved control of these diseases would be assisted by detailed epidemiological data. Here we used longitudinal, serological data to determine the patterns of exposure to Theileria parva, Theileria mutans, Babesia bigemina and Anaplasma marginale from 548 indigenous calves in western Kenya. The percentage of calves seropositive for the first three parasites declined from initial high levels due to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 28 publications
4
20
2
Order By: Relevance
“…The general lack of seroconversion in the control calves that died is consistent with the results of a recently published field study in a buffalo-free area ( Kiara et al., 2014 ) as well as a study assessing cattle exposed to T. parva from buffalo ( Mbizeni et al., 2013 ). This is presumably due to the animals dying before an antibody response has been generated, combined with generalized dysfunction of the immune system as a consequence of pathology caused by the infection.…”
Section: Discussionsupporting
confidence: 88%
“…The general lack of seroconversion in the control calves that died is consistent with the results of a recently published field study in a buffalo-free area ( Kiara et al., 2014 ) as well as a study assessing cattle exposed to T. parva from buffalo ( Mbizeni et al., 2013 ). This is presumably due to the animals dying before an antibody response has been generated, combined with generalized dysfunction of the immune system as a consequence of pathology caused by the infection.…”
Section: Discussionsupporting
confidence: 88%
“…In a previous study by the group ( Kiara et al, 2014 ), the antibody responses to four of the tick-borne parasites present in the study region ( T. parva , T. mutans , A. marginale and B. bigemina ) were measured by ELISA for each calf at each 5-week time point and analyzed to determine the number of calves that seroconverted to these parasites during the study period. The results revealed that 77% of the calves seroconverted to T. parva , 82% to T. mutans , 50% to A. marginale , and 36% to B. bigemina ( Kiara et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study by the group ( Kiara et al, 2014 ), the antibody responses to four of the tick-borne parasites present in the study region ( T. parva , T. mutans , A. marginale and B. bigemina ) were measured by ELISA for each calf at each 5-week time point and analyzed to determine the number of calves that seroconverted to these parasites during the study period. The results revealed that 77% of the calves seroconverted to T. parva , 82% to T. mutans , 50% to A. marginale , and 36% to B. bigemina ( Kiara et al, 2014 ). When compared to the adjusted prevalences of these parasites as estimated by RLB (12.1%, 71.6%, 0% and 0.2%, respectively), it is clear that many of the infections with these parasites, apart from T. mutans , appear to have been resolved to the extent that the blood stages of the parasites are no longer detectable at 51 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…In Kenya, TBPs (including viral diseases—arboviruses) like Crimean Congo hemorrhagic fever (CCHF), Dugbe, Kupe, and Hazara, as well as hemoparasites that cause babesiosis, theileriosis, and rickettsiosis, are major impediments to livestock productivity and public health (36). …”
Section: Introductionmentioning
confidence: 99%